PELAKSANAAN PEMBIAYAAN DANA TALANGAN HAJI PADA PERBANKAN SYARIAH - Erni Susana; Diana Kartika (University of Merdeka Malang, 2013)
The syariah banking activity was basically the expansion of banking service for people who needed it andexpected the repayment which was not based on interest rate, but based on syariah as what determined inIslamic law. To help people to get pilgrim portion soon, syahriah banking offered agreement which was usedin financing pilgrim lending fund like al-qardh agreement and al-ijarah (ujroh system). The aim of thisresearch was to analyze financing using al-qardh agreement and al-ijarah (ujroh system) agreement. Al-qardhwas giving wealth to other people that could be collected back or asked for, or in other words lending withoutexpecting repayment, while the meaning of al-ijarah agreement was an agreement of moving the use or utilizationright on goods and service, through rent payment or ujroh without being followed by transferringownership. The implementation of financing pilgrim lending fund conformed to the rule of financing pilgrimarrangement which was written in Fatwa (a binding ruling in religious matters) DSN No. 29/DSN-MUI/VI/2002. The amount of al-ijarah repayment was not based on the amount of lending al-qardh given to thecustomers.